A comparative study of value-added mobile services in Finland and Taiwan. (7th February 2006) - Sun, Szu-Yuan; Ju, Teresa L.; Su, Chao-Fan
Mobile commerce, or e-commerce over mobile devices, has become a major interest for the IS research community. We surveyed the three largest cell phone service providers in Taiwan and sorted these providers' value-added services using the eight categories of Balasubramanian et al. and Clarke's four-value propositions for m-commerce to examine each value-added service's characteristics. We compared the results with Anckar and D'Incau's research to determine the key differences between Taiwan and Finland. The purpose of this study is to understand the characteristics and current situations of services provided in Taiwan, as well as what areas need improvement.